2015
DOI: 10.1007/s10705-015-9695-4
|View full text |Cite
|
Sign up to set email alerts
|

Climate-smart crop production in semi-arid areas through increased knowledge of varieties, environment and management factors

Abstract: In large regions of sub-Saharan Africa, semi-arid conditions are likely to increase with climate change, yet these regions are becoming more important to feed production zones due to increasing population pressure. A production system in the semi-arid south eastern Zimbabwe was studied to assess different possible growth conditions of food crop in relation to seasonal differences, spatial rainfall distribution, use of organic nutrients and different position in the landscape. The growth and yield of four crops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…The reason for farmers' choice of growing sorghum and maize, than other crops could primarily be due to the fact that they are drought tolerant, versatile and meets farmers' need for both food and cash. This is in line with a study carried out by Kudadjie et al (2004) and Murungweni (2016) which revealed sorghum and maize as climate smart crops. The second reason could be that the sorghum crop can store well under local conditions and the stems can be eaten like sugarcane by Karamoja local people.…”
Section: Crops Grown In the Study Areasupporting
confidence: 91%
“…The reason for farmers' choice of growing sorghum and maize, than other crops could primarily be due to the fact that they are drought tolerant, versatile and meets farmers' need for both food and cash. This is in line with a study carried out by Kudadjie et al (2004) and Murungweni (2016) which revealed sorghum and maize as climate smart crops. The second reason could be that the sorghum crop can store well under local conditions and the stems can be eaten like sugarcane by Karamoja local people.…”
Section: Crops Grown In the Study Areasupporting
confidence: 91%
“…This can be partially reached through growing drought-tolerant varieties while setting forth more rational strategies for exploiting landscape. The use of fertilizers and improving the soil water holding capacity represent other options (Murungweni et al, 2016). Additionally, application of innovative nanotechnologies in agriculture (including the advantageous nano-particles) has been shown to be a promising approach to improve crop production considerably (Lal, 2008;Liu & Lal, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…With a mean annual rainfall of approximately 450 mm, much of the central part of southern Africa is classified as semi-arid ( Fig 2). In fact, semi-arid conditions in SSA regions are likely to increase with climate change, yet these regions are becoming more important to feed production zones due to increasing population pressure (Murungweni et al, 2015). Production systems in semi-arid regions of the world are often thought of as being particularly vulnerable to climate change.…”
Section: Vulnerability Of Small-holder Farmer's In Developing Countriesmentioning
confidence: 99%
“…Low lying areas tend to have less risk of crop failure during a drought but can be vulnerable to flooding. Therefore, farmers in semi-arid regions can reduce risk of total crop failure by making a clever use of both the low lying and the upland areas depending on crops of their interest (Murungweni et al, 2015). The Zimbabwe-based Africa Conservation Tillage Network (ACT), recommends breaking the soil only where seeds are to be planted, as ploughing entire fields can degrade soil.…”
Section: Conservation Agriculture (Soil Water and Crop Management)mentioning
confidence: 99%
See 1 more Smart Citation